Counterfeiting in the People's Republic of China - Daniel C. K. Chow (Washington University Law Quarterly, 2000)
This Article examines counterfeiting in China, its origins, and problems in enforcement. It also provides some suggestions for alleviating the problem, and concludes with some observations about the future of counterfeiting in China. Part I of this Article examines the size, scope, and severity of the counterfeiting problem. Part II reviews the enforcement system in China, the current issues that contribute to a lack of effective enforcement, and provides some suggestions for improvement. Part III examines the issues of political will and commitment and discusses future trends.
Keywords: Product counterfeiting – China; Intellectual property; Piracy (Copyright)